Case report: Challenges and implications of conduction system pacing in pediatrics: Case series - Ploneda Valencia, Ruy Gonzalo; Levinstein Jacinto, Moisés; Sánchez Contreras, Carmen A.; Ruiz González, Gustavo; Neach de la Vega, Diego; Márquez Murillo, Manlio F.; Nava, Santiago (Frontiers in Pediatrics, 2023)
Cardiac electrical stimulation in children usually is needed in the setting of congenital atrioventricular block, after heart surgery, and in some specific channelopathies. In most cases, the percentage of ventricular stimulation is high, so there is concern on the deleterious effects of chronic stimulation of the right ventricle. In recent years, physiologic stimulation has developed as a valid approach for adult patients and a great interest has arisen in offering conduction system pacing also to the pediatric population. We present 3 pediatric cases of stimulation of the conduction system (His bundle or left bundle branch), in order to show the intrinsic particularities and challenges implied in these techniques.